علاقة الرؤية والرسالة الارتباطية بالصورة الذهنية لبرنامج المکتبات والمعلومات بکلية الآداب جامعة المنوفية: دراسة حالة لبرنامج معتمد - د. نها عثمان (المجلة الدولية لعلوم المكتبات والمعلومات)
The study focused on the effect of vision and mission on the mental image of the Library and Information Program at the Faculty of Arts, Menoufia University. In this study, two approaches were used: the first approach is the “case study” approach, through which the requirements for formulating and publishing the mission and vision for that program were studied and compiled as one of the program accreditation standards in accordance with the National Authority for Quality Assurance and Accreditation Standards. The second one is “Analytical Descriptive approach” which is concerned with investigating the opinions of students from the studied program by using a questionnaire composed of 10 questions categorized under 3 axes. It was applied to a sample of 83 students (male and female) from the second year in the studied Program. The statistical analyses showed that 70 students (84%) admitted a positive effect, while 13 students (16%) gave a negative effect of the mission of the Library and Information Program in changing their mental image regarding the level of the department’s graduates and the extent of the department’s responses to meet the needs of the local and regional labor market with respect to them. One of the most important recommendations in this study is a great consideration should be given to the students ’opinions during the preparation of the vision and mission for the library and information programs in the college, because they are the main output of the educational process and the main goal when re-applying for accreditation.